Synthesised Conductive/Magnetic Composite Particles for Magnetic Ablations of Tumours - Chiang-Wen Lee; Ju-Fang Liu; Wen-Chun Wei; Ming-Hsien Chiang; Ting-Yuan Chen; Shu-Hsien Liao; Yao-Chang Chiang; Wen-Cheng Kuo; Kuen-Lin Chen; Kuo-Ti Peng; Yen-Bin Liu; Jen-Jie Chieh (Micromachines, 2022)
Ablation is a clinical cancer treatment, but some demands are still unsatisfied, such as electromagnetic interferences amongst multiple ablation needles during large tumour treatments. This work proposes a physical synthesis for composite particles of biocompatible iron oxide particles and liquid metal gallium (Ga) with different alternative-current (AC)-magnetic-field-induced heat mechanisms of magnetic particle hyperthermia and superior resistance heat. By some imaging, X-ray diffraction, and vibrating sample magnetometer, utilised composite particles were clearly identified as the cluster of few iron oxides using the small weight ratio of high-viscosity liquid metal Ga as conjugation materials without surfactants for physical targeting of limited fluidity. Hence, well penetration inside the tissue and the promotion rate of heat generation to fit the ablation requirement of at least 60 °C in a few seconds are achieved. For the injection and the post-injection magnetic ablations, the volume variation ratios of mice dorsal tumours on Day 12 were expressed at around one without tumour growth. Its future powerful potentiality is expected through a percutaneous injection.